The identity of Utricularia trinervia (Lentibulariaceae): Taxonomic re-establishment and unpublished descriptions of trap morphology - Guedes, Felipe Martins; Coan, Alessandra Ike [UNESP]; Araujo, Giselle Bezerra [UNESP]; Alves, Marccus (Wiley-Blackwell, 2021)
Previous morphometric and molecular studies indicate that Utricularia amethystina is a species complex distributed in the warmer zones of the Neotropical region. It includes 31 names accepted as synonyms, mainly based on morphological characteristics of bracts and bracteoles, traps and capsule dehiscence. Despite previous efforts and evidence suggesting that at least four names should be reconsidered at species level, this taxonomic complex still needs improved resolution and recircumscription for each species. Therefore, this contribution presents macro- and micromorphological evidence for the re-establishment of U. trinervia, including its detailed taxonomic description, unprecedented characterization of its traps, habitat and distribution, conservation status and comparative discussion with U. amethystina s.str.
Keywords: carnivorous plants; Neotropics; SEM analysis; species complex; synonym; taxonomy